The Socioeconomic Impacts of Breast Cancer on Breast Cancer Patients in Penang - Yen Siew Hwa,; Aishah Knight Abd Shatar,; Hasnah Hashim, (Kajian Malaysia, 2011)
Breast cancer is a major cause of death and is the most common type of cancer among Malaysian women, accounting for more than 30% of newly diagnosed cancer cases in this population. In 2006, the National Cancer Registry recorded 3,525 cases of female breast cancer in Peninsular Malaysia. In addition to facing uncertainties, anxieties, possible disabilities and the fear of death, some breast cancer patients must deal with increased treatment-related expenses, loss of employment and consequent loss or reduction of income. This study examined the socioeconomic impact of breast cancer on breast cancer patients in Penang, Malaysia. The study involved 60 respondents, including 20 patients undergoing treatment at private hospitals and 40 patients undergoing treatment at public hospitals. Data were collected using guided interviews, which were later quantified for further analyses. Our study showed that all of the respondents who were working prior to their diagnosis were adversely affected. The most seriously affected patients were those who had to stop working and consequently lost 100% of their incomes. Another group of patients suffered pay cuts because they had to limit their working hours or opted to work part-time. Most of the adversely affected cases were from lower income groups and were either self-employed or working in the private sector. The financial burdens resulting from extra medical and non-medical expenses and lost income caused financial difficulty for some respondents. Despite these adverse economic impacts, the respondents appeared to have coped relatively well socially. They also claimed to have adequate support from family and friends